Policy developer's perceptions on the implementation of National Health Insurance in South Africa: a qualitative study - Vivian Naidoo; Fatima Suleman; Varsha Bangalee (Taylor & Francis Group, 2023)
Abstract Background Universal health coverage has gained significant momentum internationally as the policy solution to address healthcare system deficiencies and promote equitable distribution of quality healthcare. The South African government has adopted this option and developed policy papers for discussion on a National Health Insurance (NHI) system for South Africa. A large part of the policy has been focused on promoting functionality of the primary healthcare system (PHC); to promote an efficient referral pathway. This study sought to explore potential barriers perceived by policy developers that could hinder achieving the NHI goal. Furthermore, given that a large focus is centred on PHC re-engineering, it was imperative to understand participant's opinions and perspectives on the role of a pharmacist at this level. Methods A qualitative research design was adopted in this study. Semi-structured interviews were conducted with ten policy developers that were selected via a referral technique. These were audio recorded using a digital voice recorder on an online platform, transcribed verbatim and saved on Microsoft Word® documents. NVivo®, was utilized to facilitate the analysis of data. A thematic analytical approach was used to categorize codes into themes. Results The findings revealed that participants were in agreement that healthcare system reform is crucial in promoting equitable distribution of healthcare services in South Africa. However, the reality of this is dependent on addressing key concerns perceived by participants that have been reported as three major themes: (1) the benefit of NHI implementation; (2) concerns about NHI implementation; (3) implications for pharmacy. Conclusions South Africa is in the second phase of NHI implementation. This phase is focused on the development of sound NHI legislation and structures. This study identified a number of concerns regarding legislative anomalies and role-player involvement that could compromise the efficient implementation of NHI.